2019
DOI: 10.1103/physrevresearch.1.023016
|View full text |Cite
|
Sign up to set email alerts
|

High-harmonic generation at the nanoscale boosted by bound states in the continuum

Abstract: Recent progress in nanoscale optics is driven by the physics of electric and magnetic resonances supported by high-index dielectric nanoparticles. Here, we exploit optical bound states in the continuum in a subwavelength particle enhanced by an engineered substrate undergoing an epsilon-near-zero transition from an insulator to a conductor, and uncover how to boost dramatically high-order parametric nonlinear effects. Our strategy makes feasible an observation of a variety of multistep cascaded and multifreque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
81
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(85 citation statements)
references
References 47 publications
(81 reference statements)
2
81
0
Order By: Relevance
“…Induced energy leakage can be compensated by inserting a reflective layer of metal of epsilon-near-zero material inside the substrate at the optimal distance. [34] The thickness adjustment of the spacer between the resonator and the reflective layer allows for control of the phase of reflection and even increase of the Q factor with respect to a free-standing resonator up to several times. [10] To determine the performance of supercavity modes, we compare the Q factor of supercavities with the Q factor of the fundamental dipole mode Q md of the cylindrical resonator (Table 1).…”
mentioning
confidence: 99%
“…Induced energy leakage can be compensated by inserting a reflective layer of metal of epsilon-near-zero material inside the substrate at the optimal distance. [34] The thickness adjustment of the spacer between the resonator and the reflective layer allows for control of the phase of reflection and even increase of the Q factor with respect to a free-standing resonator up to several times. [10] To determine the performance of supercavity modes, we compare the Q factor of supercavities with the Q factor of the fundamental dipole mode Q md of the cylindrical resonator (Table 1).…”
mentioning
confidence: 99%
“…A similar study showed similar findings with a 600-fold enhancement of third-harmonic generation from silicon arrays compared to bare films. [70] The experimental verification of [81] has been carried our recently confirming an enhanced second-harmonic generation from individual AlGaAs nanoscale resonators. [56] Using a combination of quasi-BIC on an ENZ substrate enabled a relatively high-Q factor in the telecommunication regime.…”
Section: Bics For Harmonic Generationmentioning
confidence: 97%
“…The BIC, in the case of a PhC slab, corresponds to the mode that lies inside the light cone but is nevertheless nonradiative, either because of symmetry protection or because of destructive interference between different radiation channels [33][34][35]. BICs have been theoretically proposed and experimentally implemented to enhance nonlinear generation in singly resonant regime [36][37][38]. The doubly resonant PhC cavity design [32] abandoned the commonly held notion of engineering photonic bandgaps at both FH and SH frequencies.…”
Section: Introductionmentioning
confidence: 99%